Joan Mary Anderson. 12 May 1932—28 August 2015. (25th December 2018) - Horton, Peter; Chow, Wah Soon; Barrett, Christopher
Abstract : Joan Mary (Jan) Anderson pioneered the investigation of the molecular organization of the plant thylakoid membrane, making seminal discoveries that laid the foundations for the current understanding of photosynthesis. She grew up in Queenstown, New Zealand, obtaining a BSc and MSc at the University of Otago in Dunedin. After completing her PhD at the University of California, she embarked on a glittering career at CSIRO and then the Australian National University in Canberra. Not only a gifted experimentalist, Jan was a creative thinker, not afraid to put her insightful and prophetic hypotheses into the public domain. Her many notable achievements include establishing the details and the physiological significance of lateral heterogeneity in the distribution of the two photosystems between stacked and unstacked thylakoid membranes and the dynamic changes in the extent of stacking that occur in response to changes in the light environment. Her investigations brought her into collaboration with leading researchers throughout the world. Recognized with many honours as a leading scientist in Australia, international recognition included the Lifetime Achievement Award from the International Society of Photosynthesis Research and honorary fellowships at universities in the UK and USA.